Detection of pathogenic bacteria in large volume food samples using an enzyme-linked immunoelectrochemical biosensor. (January 2021) - Capobianco, Joseph A.; Armstrong, Cheryl M.; Lee, Joe; Gehring, Andrew G.
Abstract: Increased speed and sensitivity of testing are always desired for the detection of pathogens in foods. Presented a test sample with low microbial analyte concentration, it is an advantage to analyze as much volume as possible of the sample to attain the best limit of detection (LOD). Therefore, a rapid screening method using a novel flow-through immunoelectrochemical biosensor was developed for the detection of pathogenic bacteria ( E. coli O157:H7 and Salmonella ) in food (ground beef). As the working electrode employed was comprised of a porous, antibody-coated graphite felt electrode that served as both a biorecognition-element coated solid support for capture of targeted pathogens as well as a signal transducer, high volumes of aqueous sample could be rapidly exposed to the solid support via gravity flow. Flow rates as high as 16.7 mL/min and 12.3 mL/min could be achieved for bacterial samples in buffer and 1:4 ground meat (beef) homogenate, respectively, with no significant effect on LOD. Fastest flow rates for beef homogenate, without clogging of the porous electrode as well as reduction in apparent electrochemical interference, was realized with a tandem combination of sample pretreatment strategies that included filtration with glass wool and graphite felt as well as continuous flow centrifugation. The LOD for 10, 000 E. coli O157 cells in 5, 60, and 1000 mL of buffer was 2000, 170, and 10 cells/mL, respectively in a total assay time of 3 h whereas the LOD for E. coli O157 was 400 cells/mL in 1:4 beef homogenate. Highlights: Rapid, field portable biosensor for detecting microbial pathogen in foods. Flow-through system enables screening of large sample volumes without subsampling. The working electrode serves as selective capture surface and as signal transducer.